A Scoping Review of Green Supply Chain and Company Performance - Endah Prawesti Ningrum; Arissetyanto Nugroho; Darmansyah Darmansyah; Nurmala Ahmar (Research Collaboration Community (RCC), 2024)
Environmental pollution is a serious problem that can cause the extinction of living things on earth if it is not addressed immediately. Implementing a green supply chain is one form of company attention to answer these demands. This research aims to analyze the influence of green supply chains on company performance. This research was carried out using the literature review method by reviewing various previous studies contained in various electronic journal or literature search databases. The results of this research found that the green supply chain is an important strategy for achieving sustainable development for companies. The biggest driving factors for implementing a green supply chain usually come from outside the company, namely government regulations and environmentally conscious customers. Companies must also evaluate product design and production techniques and presentation in order to produce products that are more environmentally friendly.